(untitled) (Docentes 2.0 Journal, 2020)
The events that characterize microlearning, are constituted in representative priorities of the dynamics that dominates the need for updating, innovation and better performance profiles within the surrounding reality of technology and super-information, in which education cannot be distanced. The present essay aimed to reflect on the need for constant training and education of the university teacher, regarding the knowledge of specific aspects related to the management of technology, related to the resources and strategies of microlearning; it was developed on the basis of sections interconnected to the mentioned tool, distinguished as microlearning: innovative pedagogy; social learning as the core of microlearning, aspects of interest of microlearning for the teacher and conclusions. Among the latter, it was identified the fact that microlearning allows university teachers to transcend in an intelligent, creative and motivating way in front of their academic activities, adjusting their activities to digital environments, where the need for self-management in educational processes is evident.